PENEGAKAN HUKUM PIDANA LINGKUNGAN OLEH DIREKTORAT RESERSE KRIMINAL KHUSUS KEPOLISIAN DAERAH RIAU TERHADAP PELAKU PEMBAKARAN HUTAN DAN LAHAN - Agung Setio Apriyanto; Maria Maya Lestari; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Smoke catastrophic events caused by land and forest fires in Riau Province has become a very worrying problem, this situation is like an annual agenda for the people of Riau province that has been exposed to smoke on a regular basis over the last 17 years ie since 1997. Disaster smoke in the Riau Province The background background by burning peat. If the result of fires and peat continued every year, then in the next five years remaining natural forests of Riau only <20%. Event of forest fire occurrence is not the least because of the element of intent, with a view to the opening of oil palm plantations, forest plantations, transmigration and so forth. However, to date, no environmental criminal law enforcement operate effectively even cases of forest fires and land each year show an increase in numbers.The purpose of this thesis, namely: First, to determine the implementation of environmental criminal enforcement by the Directorate of Criminal Investigation Special Riau Police against the perpetrators of forest and land fires. Second, to determine the constraints faced by the Directorate of Criminal Investigation Special Riau Police in environmental criminal enforcement against perpetrators of forest and land fires, and third, to find out the efforts made by the Special Criminal Investigation Directorate Riau Police to overcome obstacles in the enforcement of criminal law environment against the perpetrators of forest and land fires. This type of research is classified in legal studies is defined sociological look at the effectiveness of the law in force to see the correlation between the legal community.From the results of research and discussion, it can be concluded that the First, implementation of environmental criminal enforcement by the Directorate of Criminal Investigation Special Riau Police against the perpetrators of forest and land fires is done by means of preventive and repressive, Second, constraints faced by the Directorate of Criminal Investigation Special Police in Riau environmental criminal enforcement against perpetrators of forest and land fires are internal constraints and external constraints, and the efforts made by the Third Special Criminal Investigation Directorate Riau Police to overcome the obstacles in environmental criminal enforcement against perpetrators of forest and land fires is to maximize internal factors and externally owned by the Directorate of Criminal Investigation Special Riau Police.Keywords: Law Enforcement - Criminal Environment - Land and Forest Fire